4,5-Dimethoxy-2-nitrobenzohydrazides and 1-(1-Benzylpiperidin-4-yl)ethan-1-ones as Potential Antioxidant/Cholinergic Endowed Small Molecule Leads - Rukhsar Banu; Jason Gerding; Cynthia Franklin; Donald Sikazwe; William Horton; Marianna Török; Julian Davis; Kwan H. Cheng; Muziya Nakazwe; Bereket Mochona (MDPI AG, 2017)
The objective of this research is to generate leads for developing our ultimate poly-active molecules with utility in central nervous system (CNS) diseases. Indeed, poly-active molecules capable of mitigating brain free radical damage while enhancing acetylcholine signaling (via cholinesterase inhibition) are still being sought for combating Alzheimer's disease (AD). We differentiate "poly-active" agents from "multi-target" ones by defining them as single molecular entities designed to target only specific contributory synergistic pharmacologies in a disease. For instance, in AD, free radicals either initiate or act in synergy with other pharmacologies, leading to disease worsening. For this preliminary report, a total of 14 (i.e., 4,5-dimethoxy-2-nitrobenzohydrazide plus 1-(1-benzylpiperidin-4-yl)ethan-1-one) derivatives were synthesized and screened, in silico and in vitro, for their ability to scavenge free radicals and inhibit acetylcholinesterase (AChE)/butyrylcholinesterase (BuChE) enzymes. Overall, six derivatives (4a, 4d, 4e, 4f, 4g, 9b) exhibited potent (>30%) antioxidant properties in the oxygen radical absorbance capacity (ORAC) assay. The antioxidant values were either comparable or more potent than the comparator molecules (ascorbic acid, resveratrol, and trolox). Only three compounds (4d, 9a, 9c) yielded modest AChE/BuChE inhibitions (>10%). Please note that a SciFinder substance data base search confirmed that most of the compounds reported herein are new, except 9a and 9c which are also commercially available.